Effectiveness of Theft Investigation by Investigation Unit I of the Pidum Satreskrim at Ngawi Police - Sitanggang, Hizkia Krisolit (Advances in Police Science Research Journal, 2024)
A crime that often occurs in the jurisdiction of Ngawi Police Station is theft with aggravation. The increasing number of cases is caused by several factors. One of them is the lack of sufficient personnel to handle and handle the large number of incoming cases. Other factors include supporting tools for the case investigation process such as witnesses and evidence at the scene that does not exist. Violent theft should no longer occur as it will disrupt the balance of society. The author wants to know, explore and get a clear and real picture of how the investigation conducted by Satreskrim against the crime of stealing in 2020 to 2022 in the jurisdiction of Ngawi Police, by going directly to the field conducting interviews with sources of information and observing documents to get maximum research results. It is hoped that by using this method, it can provide complete information in accordance with the actual situation.